COACHING BEHAVIORAL ASPECTS THROUGH PHYSICAL EDUCATION : LITERATURE REVIEW - Raffiandy Alsyifa Putra; Phil Yanuar Kiram; padli padli; Fiky Zarya (MAJORA: Majalah Ilmiah Olahraga, 2022)
The focus of the data that will be displayed in the literature of this review is at least aimed at describing the education, physical activity, character building of children in the school period. The research method used is literature review by following the literature review procedure. Using keywords on google scholar "character" and "physical education". Character can determine a person in the way of thinking, behaving, and acting that becomes a habit displayed in social life. Individuals with good character are individuals who can make decisions and are ready to account for any consequences of the decisions made. In the current era of globalization, rapid development continues to occur in all aspects of human life, all these advances not only have a positive impact, but also have a negative impact. The emergence of various behavioral shifts, especially students, that are contrary to the culture, norms, rules, and ethics that exist in society, the increasing number of brawls between students, and other forms of juvenile delinquency in big cities. The findings of character education can be formed, one of which is through physical education and sports (gymnastics), through motor activities that are carried out continuously, so that it becomes a habit. Physical education is essentially an educational process that utilizes physical activity to produce holistic changes in individual qualities, both in physical, mental, and emotional terms.